PerioGlasU acts on human stem cells isolated from peripheral blood - Vincenzo Sollazzo; Annalisa Palmieri; Luca Scapoli; Marcella Martinelli; Ambra Girardi; Furio Pezzetti; Paolo Morselli; Francesca Farinella; Francesco Carinci (Wolters Kluwer Medknow Publications, 2010)
Background: PerioGlasO (PG) is an alloplastic material used for grafting periodontal osseous defects since 1995. In animal models, it has been proven that PG achieves histologically good repair of sur-gically created defects. In clinical trials, PG was effective as an adjunct to conventional surgery in the treatment of intrabony defects. Because the molecular events due to PG that are able to alter osteob-last activity to promote bone formation are poorly understood, we investigated the expression of os-teoblastic related genes in mesenchymal stem cells exposed to PG. Methods: The expression levels of bone related genes like RUNX2, SP7, SPP1, COL1A1, COL3A1, BGLAP, ALPL, and FOSL1 and mesenchymal stem cells marker (CD105) were analyzed, using real time reverse transcription-polymerase chain reaction. Pearson's chi-square (χ2 ) test was used to detect markers with significant differences in gene expression. Results: PG caused induction of osteoblast transcriptional factor (like RUNX2), bone related genes osteopontin (SPP1), osteocalcin (BGLAP) and alkaline phosphatase (ALPL). All had statistical sig-nificant P values (< 0.05). Conclusion : PG has a differentiation effect on mesenchymal stem cells derived from peripheral blood. The obtained results can be relevant to better understanding of the molecular mechanism of bone regeneration and as a model for comparing other materials with similar clinical effects.